Selective Solid-Phase Extraction of Pb(II) Ions Using an Ion-Imprinted Functionalized Sodium Trititanate Whisker Adsorbent Prepared by a Surface-Imprinting Technique - Wanzhen Xu; Wenming Yang; Wei Zhou (Adsorption Science & Technology)
Lead(II) ion-imprinted functionalized sodium trititanate whisker polymers [Pb(II)-IIPs/Na 2 Ti 3 O 7 ] for solid-phase extraction (SPE) were prepared by the copolymerization of Pb(II) as the template ion, chitosan (CTS) as the functional monomer and γ-glycidoxypropyl trimethoxysilane (KH-560) as the linking agent in the presence of sodium trititanate whiskers (Na 2 Ti 3 O 7 ) as the carrier. The Pb(II)-IIPs/Na 2 Ti 3 O 7 materials capable of selectively adsorbing Pb(II) ions thus obtained were used for the pre-concentration and determination of the Pb(II) ion concentration in Chinese traditional medicine samples. The prepared sorbent was characterized by Fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). A series of batch adsorption experiments was performed to evaluate the adsorption behaviour of the Pb(II)-IIPs/Na 2 Ti 3 O 7 materials towards Pb(II) ions, as assessed by inductively coupled plasma–atomic emission spectrometry (ICP–AES). The maximum adsorption capacity, the distribution coefficient (K d ) and the relative selectivity coefficients (k′) of Pb(II)-IIPs for Pb(II)/Co(II), Pb(II)/Cd(II), Pb(II)/Cu(II), Pb(II)/Hg(II), Pb(II)/Mg(II), Pb(II)/Mn(II), Pb(II)/Zn(II) and Pb(II)/Ni(II) were calculated. Compared with non-ionimprinted polymers functionalized sodium trititanate whisker polymers (non-IIPs/Na 2 Ti 3 O 7 ), the Pb(II)-IIPs/Na 2 Ti 3 O 7 material had a higher selectivity towards Pb(II) ions. The relative selectivity factor (k′) values were all greater than 2.5. The developed method was successfully applied to the determination of the amounts of trace Pb(II) ions in traditional Chinese medicine samples with satisfactory results.